Dyad of pain and depression in chronic rhinosinusitis. Issue 3 (19th November 2015) - Cox, Daniel R.; Ashby, Shaelene; DeConde, Adam S.; Mace, Jess C.; Orlandi, Richard R.; Smith, Timothy L.; Alt, Jeremiah A.
Abstract : Background: Pain and depression often coexist as comorbidities in patients with chronic disease and exert a major impact on quality of life (QOL). Little is known about the relationship between pain and depression in chronic rhinosinusitis (CRS). Our objective was to investigate this relationship and to analyze the effect of pain and depression on QOL in CRS. Methods: Patients with CRS were prospectively recruited as part of an observational cohort study. A total of 70 participants provided pain scores using both the Brief Pain Inventory Short Form (BPI‐SF) and the Short Form McGill Pain Questionnaire (SF‐MPQ). Patients at risk for depression were identified using the Patient Health Questionnaire–2 (PHQ‐2). CRS‐specific QOL was determined using the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). Results: Significant positive correlations were found between depression scores and all pain measures ( R = 0.475 to 0.644, p < 0.001). Patients with a PHQ‐2 score ≥1 had significantly higher scores on all reported pain measures. Significant positive correlations were found between all pain measures, the total SNOT‐22 score, and 3 SNOT‐22 subdomains (sleep, psychological dysfunction, and ear/facial symptoms; R = 0.323 to 0.608, p < 0.05). Conclusion: Adult patients with CRS at risk for depression experience more pain and have overall worse disease‐specific QOL. Further research investigating the complex interactions between depression and pain and the role it plays in CRS disease‐specific QOL is warranted.